1998
DOI: 10.1007/s002449900367
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Bioaccumulation of Contaminants from Sediments of the Upper Mississippi River Using Field-Collected Oligochaetes and Laboratory-Exposed Lumbriculus variegatus

Abstract: Concern with the redistribution of contaminants associated with sediment in the upper Mississippi River (UMR) arose after the flood of 1993. This project is designed to evaluate the status of sediments in the UMR and is one article in a series designed to assess the extent of sediment contamination in navigational pools of the river. Companion articles evaluate sediment toxicity and benthic community composition in navigation pools of the river. The objectives of the present study were to: (1) to assess the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 18 publications
5
60
0
2
Order By: Relevance
“…A 28-d laboratory exposure has been suggested as a standard, because this typically results in tissue residues within 80% of steady state [10]. This test duration has been validated in a number of studies that found reasonable agreement between tissue residues of field-collected and laboratory-exposed organisms, including for most PCDD/F congeners [21][22][23][24][25]. This comparative approach assumes that organisms in both the laboratory and the field have reached steady-state concentrations.…”
Section: Comparison: Laboratory and Field Methodsmentioning
confidence: 99%
“…A 28-d laboratory exposure has been suggested as a standard, because this typically results in tissue residues within 80% of steady state [10]. This test duration has been validated in a number of studies that found reasonable agreement between tissue residues of field-collected and laboratory-exposed organisms, including for most PCDD/F congeners [21][22][23][24][25]. This comparative approach assumes that organisms in both the laboratory and the field have reached steady-state concentrations.…”
Section: Comparison: Laboratory and Field Methodsmentioning
confidence: 99%
“…Other PAHs, as well as DDE and DDD, appeared to reach steady-state between 14 and 28 d. This study also compared steady-state concentrations from laboratory exposures with field-collected oligochaetes and found that concentrations in tissue were similar. Other comparisons of 28-to 30-d laboratory exposures with field-collected oligochaetes found that organisms accumulated similar concentrations of PAHs [54] and PCBs [24]. However, it was observed that concentrations of highly chlorinated PCB congeners (hepta to deca) were slightly higher in field organisms, suggesting that 30 d was insufficient for these very hydrophobic compounds (log K OW > 7) to reach steady-state in the laboratory [24].…”
Section: Exposure Techniquesmentioning
confidence: 96%
“…The concentration of TOC in sediment also may influence the bioavailability of contaminants through sorption/desorption, causing increased variability in BSAFs between sites. Many researchers now calculate a BSAF in which the concentration of the organic contaminant is normalized to both lipid and sediment organic carbon [37,44,54]. The resulting BSAF has the units organic carbon/ lipid and is theoretically independent of species or sediment type.…”
Section: Quality Of the Overlying Watermentioning
confidence: 99%
“…Les conditions de culture de Lumbriculus variegatus sont détaillées dans Phipps et al (1993) (1), Brunson et al (1998) (2), ASTM (2000) (3), U.S. EPA (2000) (4). Un bref résumé de ces conditions est présenté cidessous.…”
Section: Méthodes De Cultureunclassified
“…Les animaux endobenthiques qui ingèrent des sédiments sont soumis à un risque d'exposition substantielle aux substances liées aux sédiments, et soulèvent par conséquent un grand intérêt, par exemple (1), (2), (3). Parmi les organismes de ce type, les oligochetes aquatiques jouent un rôle important dans les sédiments des systèmes aquatiques.…”
unclassified